Pengaruh Keberhasilan Penyuluhan Pertanian Dengan Menggunakan Alat Peraga (Study Kasus di Desa Sumengko Kecamatan Duduk Sampeyan Kabupaten Gresik) - Emmy Hamidah (AGRORADIX : Jurnal Ilmu Pertanian, 2022)
Agricultural development cannot be carried out by farmers alone, because agriculture cannot develop beyond the subsystem stage without appropriate developments in other areas of the nation's life, where agriculture is carried out. In accordance with the direction of agricultural development, extension agents have a very important role which must be placed in a larger context, namely development extension agents. The aim of the study was to find out how far the influence of the use of visual aids in the delivery of agricultural extension materials to farmers was compared to if the extension did not use props. The research sample was determined using a stratified random sampling method. While the method of data analysis used the Chi Square Test. The results of the study Shows that the use of teaching aids in counseling has a very positive effect on the sample farmers, so that they can systematically follow the flow of the material presented, the level of understanding is higher and the impression is stronger in their minds. Sample farmers avoid feeling bored during counseling. The motivator is more stable in conveying the material. Differences in the age of sample farmers showed no significant difference in material acceptance.